2013
DOI: 10.1128/aac.00161-13
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Consequences of Plasmodium falciparum pfmdr1 Polymorphisms Inferred from Ex Vivo Culture of Ugandan Parasites

Abstract: bPolymorphisms in the Plasmodium falciparum multidrug resistance 1 (pfmdr1) gene impact sensitivity to multiple antimalarials. In Africa, polymorphisms at N86Y and D1246Y are common and have various impacts on sensitivity to different drugs. To gain insight into the fitness consequences of these polymorphisms, we cultured parasites isolated from children with malaria in Tororo, Uganda, where the multiplicity of infection is high, and used pyrosequencing to follow polymorphism prevalences in culture over time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…We evaluated the complexity of infections using the msp1 block 2 allele types and several polymorphic sites of genes associated with drug resistance. Consistent with findings from other endemic areas (Nsobya et al, 2008; Ochong et al, 2013), we observed a trend of gradual decrease of parasite populations during culture, suggesting that some parasites are less fit. A large proportion of the parasites essentially became monoclonal during in vitro culture for 3–4 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We evaluated the complexity of infections using the msp1 block 2 allele types and several polymorphic sites of genes associated with drug resistance. Consistent with findings from other endemic areas (Nsobya et al, 2008; Ochong et al, 2013), we observed a trend of gradual decrease of parasite populations during culture, suggesting that some parasites are less fit. A large proportion of the parasites essentially became monoclonal during in vitro culture for 3–4 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies on in vitro parasite competition performed thus far focused on genetically defined laboratory strains (Hayward et al, 2005; Peters et al, 2002) and clinical isolates from high-transmission areas where complexity of infection is high (Nsobya et al, 2008; Ochong et al, 2013). In this study, we assessed the competition between parasite populations in mixed clinical infections from a hypoendemic area near the China-Myanmar border during in vitro culture adaption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering impacts of pfmdr1 polymorphisms on the fitness of clinical isolates, P. falciparum was cultured from children with malaria in a region of Uganda with high multiplicity of infection (and thus high likelihood of mixed infections), and changes in the prevalence of the pfmdr1 N86Y and D1246Y alleles were followed over time (Ochong et al ., ). Most cultures did not undergo changes in culture, but for those that did show selection 8/11 selected towards mutant 86Y, 9/14 selected towards wild‐type D1246, and 5/7 with selection at both alleles selected towards 86Y and D1246.…”
Section: Drug Resistance and Fitness In Malaria Parasitesmentioning
confidence: 97%